A naturally occurring InDel variation in BraA.FLC.b (BrFLC2) associated with flowering time variation in Brassica rapa - Wu, Jian (BioMed Central, 2012)
BACKGROUND: Flowering time is an important trait in Brassica rapa crops. FLOWERING LOCUS C (FLC) is a MADS-box transcription factor that acts as a potent repressor of flowering. Expression of FLC is silenced when plants are exposed to low temperature, which activates flowering. There are four copies of FLC in B. rapa. Analyses of different segregating populations have suggested that BraA.FLC.a (BrFLC1) and BraA.FLC.b (BrFLC2) play major roles in controlling flowering time in B. rapa. RESULTS: We analyzed the BrFLC2 sequence in nine B. rapa accessions, and identified a 57-bp insertion/deletion (InDel) across exon 4 and intron 4 resulting in a non-functional allele. In total, three types of transcripts were identified for this mutated BrFLC2 allele. The InDel was used to develop a PCR-based marker, which was used to screen a collection of 159 B. rapa accessions. The deletion genotype was present only in oil-type B. rapa, including ssp. oleifera and ssp. tricolaris, and not in other subspecies. The deletion genotype was significantly correlated with variation in flowering time. In contrast, the reported splicing site variation in BrFLC1, which also leads to a non-functional locus, was detected but not correlated with variation in flowering time in oil-type B. rapa, although it was correlated with variation in flowering time in vegetable-type B. rapa. CONCLUSIONS: Our results suggest that the naturally occurring deletion mutation across exon 4 and intron 4 in BrFLC2 gene contributes greatly to variation in flowering time in oil-type B. rapa. The observed different relationship between BrFLC1 or BrFLC2 and flowering time variation indicates that the control of flowering time has evolved separately between oil-type and vegetable-type B. rapa groups.